2018
DOI: 10.1111/area.12478
|View full text |Cite
|
Sign up to set email alerts
|

“Are we losing our way?” Navigational aids, socio‐sensory way‐finding and the spatial awareness of young adults

Abstract: Recent advances in the accessibility and reliability of mobile technologies, roaming services and associated data have led to an increased use of modern navigational devices using Global Navigation Satellite Systems (GNSS). This paper reports on a study that explored concerns about over‐reliance on these navigational technologies, specifically among young people in the Global North. Based on an experiment in which participants were asked to navigate a series of different (unfamiliar) routes on foot, using diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…For those tourists who can still boast an adequate level of battery charge on their smartphones after a busy visit spent updating social media profiles with new photos whilst trying to simultaneously absorb the multi-sensory experience offered by the tourist attraction, there is further bad news. Similar neurological research has shown that people who are over-reliant on satellite navigation systems for way-finding (say, back to the hotel or to a restaurant highly rated on Tripadvisor) tend to perform worse at finding their way in the absence of their digital aid than those who rely on paper maps (McCullough and Collins, 2019). Parallel research in tourism has argued that this 'smart' technology-enabled tourist may run the risk of alienation (or "e-lienation", to use the term coined by Tribe and Mkono, 2017) from their surroundings and missing out on potentially enriching experiences offered by the tourism destination.…”
mentioning
confidence: 83%
“…For those tourists who can still boast an adequate level of battery charge on their smartphones after a busy visit spent updating social media profiles with new photos whilst trying to simultaneously absorb the multi-sensory experience offered by the tourist attraction, there is further bad news. Similar neurological research has shown that people who are over-reliant on satellite navigation systems for way-finding (say, back to the hotel or to a restaurant highly rated on Tripadvisor) tend to perform worse at finding their way in the absence of their digital aid than those who rely on paper maps (McCullough and Collins, 2019). Parallel research in tourism has argued that this 'smart' technology-enabled tourist may run the risk of alienation (or "e-lienation", to use the term coined by Tribe and Mkono, 2017) from their surroundings and missing out on potentially enriching experiences offered by the tourism destination.…”
mentioning
confidence: 83%
“…Unfortunately, coupling map complexity with modern reliance on turn-by-turn navigation means many students lack basic, or functional, cartographic literacy, including recognition of geographic features and an ability to read, use, and interpret maps (Ishikawa et al, 2008;McCullough & Collins, 2019). While cartographers have not settled on a single definition of cartographic literacy, cartographic literacy includes the ability to read, understand, use, and create maps.…”
Section: Cartographic Literacy and Writing Instructionmentioning
confidence: 99%
“…One empirical study conducted by Javadi et al (2017) showed that the use of navigational aids blocks way‐find function on the human brain. Similarly, McCullough and Collins (2019) proposed that the capacity to recall place characteristics during traveling was stronger when people have less reliance on Global Navigation Satellite Systems (GNSS). This result suggests that over‐reliance on such technology would impact human's sensory, social, and emotional experiences of journeying‐through.…”
Section: Introductionmentioning
confidence: 99%